ANALISIS PELUANG DAN TANTANGAN PERDAGANGAN PRODUK PERTANIAN INDONESIA DENGAN TIONGKOK DALAM KERANGKA APEC: STUDI KASUS PADA EKSPOR PALA DAN KAPULAGA - Damas Elvianto; Daspar (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2026)
Indonesia’s spice trade, particularly in nutmeg and cardamom, has shown significant growth in recent years, especially with China as one of the largest and rapidly expanding markets in Asia. Indonesia possesses a comparative advantage in terms of product quality, particularly in the aroma and essential oil content of its nutmeg and cardamom. However, this trade relationship also faces numerous challenges, including technical barriers to trade (TBT/SPS), inadequate infrastructure and logistics, and intense competition from other major exporters such as India and Sri Lanka. This study aims to analyze the opportunities and challenges of Indonesia–China agricultural trade within the framework of APEC, focusing specifically on nutmeg and cardamom exports. A descriptive qualitative method was employed, using secondary data from official sources and academic journals. The analysis reveals that enhancing Indonesia’s export competitiveness requires strategic actions such as trade diplomacy through APEC, product standardization, international certification, and support for farmers and SMEs. Strengthening Indonesia’s spice branding as premium spices is also crucial to increase competitiveness in the global market, particularly in China.